Acrylate polymer, dispersing agent, preparation method, electrode slurry, electrode plate and battery
By designing the composition of a novel acrylate polymer and suitable dispersant, the problems of poor dispersion, high viscosity and poor storage stability during the preparation process are solved, and the quality stability of the battery is significantly improved.
Patent Information
- Application Number
- CN202311809522.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-26
- Publication Date
- 2025-04-18
AI Technical Summary
In the preparation of electrode slurry, the problems of poor particle dispersion, high slurry viscosity, and short storage time often occur in the prior art, resulting in poor battery quality stability.
Using a novel structure acrylate polymer, a dispersant with excellent dispersion viscosity reduction and stickiness effect is prepared by designing repeat units in its molecular chain, combining volatile small molecule amine compounds and solvents, and is used to prepare an electrode slurry.
The quality stability of the battery is significantly improved, and by optimizing the composition and structure of the dispersant, the problems of poor dispersion, high viscosity and poor storage stability of the electrode slurry are solved.
Smart Images

Figure BDA0004631193850000021 
Figure BDA0004631193850000022 
Figure BDA0004631193850000032
Abstract
Description
Technical Field
[0001] The invention relates to an acrylate polymer, a dispersant, a preparation method, an electrode slurry, an electrode plate and a battery. Background Art
[0002] In recent years, with the development of new energy storage and electric vehicle fields, carbon materials represented by carbon nanotubes, graphene, and conductive carbon black and carbon-coated materials represented by lithium iron phosphate and lithium iron manganese phosphate have been widely used as electrode materials. However, due to the special particle structure and surface morphology of these carbon materials and carbon-coated materials, when no dispersant is used or traditional polyvinyl pyrrolidone dispersants are used, problems such as poor particle dispersion, high slurry viscosity, and short storage time often occur in the process of preparing electrode slurry, resulting in the slurry being unusable or requiring further treatment before use, further affecting the quality stability of the battery.
[0003] Patent application CN115975104A discloses an acrylate comb dispersant and a preparation method thereof, wherein the acrylate comb dispersant is obtained by polymerizing acrylate monomers, methacrylate monomers, unsaturated acids and unsaturated amide monomers in the presence of an initiator and a chain transfer agent, and the dispersant has a good dispersing effect on the positive electrode material of the battery. However, when the content of the unsaturated amide monomers in the copolymer is too low, it does not help the dispersion performance; and when the content of the unsaturated amide monomers is too high, it will cause the resistance of the positive electrode of the battery to deteriorate and the flexibility to decrease.
[0004] Patent application CN 116390976 A discloses a dispersant composition, which is composed of an alcohol amine compound, an acrylic polymer and a solvent, and has a good dispersing effect on carbon material conductive materials. However, the polyether acrylate structure contained in the acrylic polymer will degrade under the action of the alcohol amine compound during storage and use, resulting in loss of dispersibility and failure to meet stability requirements. Summary of the invention
[0005] The present invention overcomes the problems of poor particle dispersion, high slurry viscosity, poor storage stability, etc. that often occur in the process of preparing electrode slurry in the prior art, and provides an acrylate polymer, a dispersant, a preparation method, an electrode slurry, an electrode plate, and a battery. The preparation method of the present invention is simple, the structure of the prepared acrylate polymer is novel, and the dispersant containing the acrylate polymer can be used in the process of electrode slurry, has excellent dispersion, viscosity reduction and viscosity stabilization effects, and further improves the quality stability of the battery.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] In a first aspect, the present invention provides an acrylate polymer, which comprises a repeating unit I, a repeating unit II and a repeating unit III; based on the total mass of the acrylate polymer, the mass percentage of the repeating unit I is 30.0%-70.0%; the mass percentage of the repeating unit III is 20.0%-60.0%;
[0008] The structure of the repeating unit I is shown in formula (I):
[0009]
[0010] In each repeating unit I,
[0011] R1 is each independently hydrogen or methyl;
[0012] R2 is each independently C 10 -C 25 The alkyl group;
[0013] The structure of the repeating unit II is shown in formula (II):
[0014]
[0015]
[0016] In each repeating unit II,
[0017] R3 are each independently hydrogen or methyl;
[0018] Z is each independently hydrogen, Li + 、Na + , K + NH4 + or organic amine groups with a molecular weight of less than 150;
[0019] The structure of the repeating unit III is shown in formula (III):
[0020]
[0021] In each repeating unit III,
[0022] R4 are each independently hydrogen or methyl;
[0023] A groups are each independently -(CH2) p1 -;
[0024] In each A group, p1 is independently 0-2;
[0025] The B groups are each independently
[0026]
[0027] In each B group, R5 is independently hydrogen or methyl, and R6 is independently hydrogen, C1-C 18 The alkyl group is C2-C6 or the acyl group is C2-C6, and n1 is 4-70 each independently.
[0028] In the present invention, "in each ..., ... are each independently ..." means that in the molecular chain of the acrylic ester polymer, in different repeating units represented by the same general formula, the groups represented by the same symbol may be the same or different.
[0029] For example, "in each repeating unit I, R1 is independently hydrogen or methyl" means that in the molecular chain of the acrylic ester polymer, in different repeating units I represented by formula (I), R1 may be the same or different. Similarly, each repeating unit II and each repeating unit III have the above meanings.
[0030] For another example, it is also necessary to explain that "in each B group, R5 is independently hydrogen or methyl, and R6 is independently hydrogen, C1-C 18 The meaning of "n1 is 4-70" is that in the molecular chain of the acrylic ester polymer, in different repeating units I represented by formula (I), "n1" in each B group may be the same or different; n1 In the above, R5 may be the same or different.
[0031] In the present invention, in the acrylic ester polymer, the repeating unit I, the repeating unit II and the repeating unit III may be randomly distributed.
[0032] In the present invention, the weight average molecular weight of the acrylic ester polymer may be 10,000-70,000, for example, 28,100, 36,200, 49,600, 52,800 or 68,300.
[0033] In the present invention, the molecular weight distribution index (PDI) of the acrylic ester polymer may be no greater than 2.20, for example, 1.65, 1.75, 1.85, 1.92 or 2.15.
[0034] In the present invention, in each repeating unit I, R2 is independently C 12 -C 25 The alkyl group is preferably C 16 -C 22 Alkyl groups, such as C 18 of alkyl.
[0035] In certain specific embodiments, in each repeating unit I, R1 is methyl; R2 is C 12 of alkyl.
[0036] In certain specific embodiments, in each repeating unit I, R1 is hydrogen; R2 is C 18 of alkyl.
[0037] In certain specific embodiments, in each repeating unit I, R1 is hydrogen; R2 is C 22 of alkyl.
[0038] In certain specific embodiments, in each repeating unit I, R1 is hydrogen; R2 is C 16 of alkyl.
[0039] In the present invention, in each repeating unit II, Z is preferably hydrogen.
[0040] In the present invention, p1 in each A group is independently 0 or 1.
[0041] In the present invention, in each B group, R6 is independently a methyl group, a butyl group or an acetyl group.
[0042] In the present invention, in each B group, n1 may be 6-45, for example, 6, 9, 16, 20 or 45.
[0043] In certain specific embodiments, in each repeating unit II, R4 and R5 are both hydrogen; R6 is methyl; and p1 is 1.
[0044] In certain specific embodiments, in each repeating unit II, R4 and R5 are both hydrogen; R6 is methyl; and p1 is 0.
[0045] In certain specific embodiments, in each repeating unit II, R4 is hydrogen; R5 is methyl; R6 is butyl; and p1 is 1.
[0046] In certain specific embodiments, in each repeating unit II, R4 is hydrogen; R5 is hydrogen or methyl; R6 is acetyl; and p1 is 1.
[0047] In certain specific embodiments, in each repeating unit II, R4 is methyl; R5 is hydrogen; R6 is acetyl; and p1 is 1.
[0048] In a second aspect, the present invention provides a method for preparing an acrylate polymer, comprising the following steps: subjecting a raw material to a free radical polymerization reaction to obtain an acrylate polymer; wherein the raw material comprises a polymerizable monomer, and the polymerizable monomer comprises a monomer M-1, a monomer M-2, and a monomer M-3; based on the total mass of the polymerizable monomer, the mass percentage of the monomer M-1 is 30.0%-70.0%; the mass percentage of the monomer M-3 is 20.0%-60.0%;
[0049] The structure of the monomer M-1 is shown in formula M-1:
[0050]
[0051] Wherein, R1 and R2 are R1 and R2 as described above;
[0052] The structure of the monomer M-2 is shown in formula M-2:
[0053]
[0054] Wherein, R3 and Z are R3 and Z as described above;
[0055] The structure of the monomer M-3 is shown in formula M-3:
[0056]
[0057] Wherein, A, B and R4 are A, B and R4 as described above.
[0058] In the present invention, the monomer M-1 may be one or more of lauryl methacrylate, stearyl acrylate, behenyl acrylate and hexadecyl acrylate.
[0059] In the present invention, the mass percentage of the monomer M-1 may be 30.0%, 40.0%, 50.0%, 60.0% or 65.0%.
[0060] In the present invention, the monomer M-2 may be acrylic acid or methacrylic acid.
[0061] In the present invention, the mass percentage of the monomer M-2 may be 2.0%-20.0%, for example, 5.0%, 10.0%, 15.0% or 20.0%.
[0062] In the present invention, the monomer M-3 may be polyethylene glycol allyl methyl ether, polyethylene glycol vinyl methyl ether, polypropylene glycol allyl butyl ether, allyl polyethylene glycol polypropylene glycol acetate or methallyl polyethylene glycol acetate.
[0063] In the present invention, the average degree of polymerization of the polyol in the monomer M-3 may be 6-45, for example, 6, 9, 16, 20 or 45.
[0064] In the present invention, the mass percentage of the monomer M-3 may be 20.0%-50.0%, for example, 20.0%, 30.0%, 40.0% or 50.0%.
[0065] In the present invention, the sum of the mass percentages of the monomer M-1, the monomer M-2 and the monomer M-3 may be 90.0%-100.0%, for example, 95.0% or 100.0%.
[0066] In the present invention, the polymerizable monomers may further include monomer M-4.
[0067] Wherein, the monomer M-4 may be styrene.
[0068] In the present invention, the polymerizable monomers may not include monomers containing amino groups. The additional addition of amino groups does not bring any beneficial effect and will increase the rigidity of the polymer chain segments.
[0069] In the preparation method of the present invention, the reaction operation and conditions can be carried out according to the conventional operation and conditions of such reactions in the art.
[0070] In the present invention, the free radical polymerization reaction can be carried out in a solvent.
[0071] The solvent may be any organic solvent applicable in the art, preferably one or more of ethyl acetate, butyl acetate, propylene glycol methyl ether acetate, N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone, such as propylene glycol methyl ether acetate, N,N-dimethylformamide, butyl acetate or N-methylpyrrolidone.
[0072] In the present invention, the raw materials also include an initiator and a chain transfer agent.
[0073] The initiator may be a peroxide initiator, an azo initiator, or a redox initiator composed of a peroxide initiator and a reducing agent.
[0074] The peroxide initiator can be dibenzoyl peroxide, dilauroyl peroxide, dicumyl peroxide, isopropylbenzene hydroperoxide, methyl ethyl ketone peroxide, tert-butyl hydroperoxide, di-tert-butyl peroxide, tert-butyl peroxytivalate, tert-butyl peroxypivalate, tert-butyl peroxyisobutyrate, tert-butyl peroxy(2-ethylhexanoate), 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, tert-butyl peroxy-3,5,5-trimethylhexanoate, tert-butyl peroxide isopropylbenzene or 1,4-di-tert-butylperoxyisopropylbenzene.
[0075] The azo initiator can be azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, 1,1'-azo(cyanocyclohexane), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), azobisimidazolinylpropane, 2,2'-azobis(N-butyl 2-methylpropionamide), 2,2'-azo(2-methyl-N-(2-hydroxyethyl)propionamide), 2,2-azobisisobutylamidine dihydrochloride or 2,2'-azabis(2-imidazoline) dihydrochloride.
[0076] The reducing agent may be an amine compound, preferably tetramethylethylenediamine, N,N-dimethylaniline, N,N-dimethyl-p-toluidine, ethylenediamine, diethylenetriamine, triethylenetetramine or tetraethylenepentamine.
[0077] The initiator can be added dropwise into the reaction system in the form of an initiator solution. The solvent of the initiator solution is the same as the above-mentioned solvent. The time of the dropwise addition can be 360-420 minutes.
[0078] The chain transfer agent may be one or more of a mercaptocarboxylic acid chain transfer agent, a thiol chain transfer agent, isopropanol and hypophosphorous acid.
[0079] The mercaptocarboxylic acid chain transfer agent may be mercaptoacetic acid, 3-mercaptopropionic acid, ethyl 3-mercaptopropionate, butyl 3-mercaptopropionate, octyl 3-mercaptopropionate or trimethylolpropane tris(3-mercaptopropionate).
[0080] The mercaptan chain transfer agent may be mercaptoethanol, butyl mercaptan, hexyl mercaptan, octyl mercaptan or dodecanethiol.
[0081] The chain transfer agent can be added dropwise into the reaction system in the form of a monomer solution. The monomer solution can include a polymerizable monomer and the chain transfer agent. The solvent of the monomer solution is the same as the above-mentioned solvent. The time of the dropwise addition can be 360-420 minutes.
[0082] In the present invention, the reaction temperature of the free radical polymerization reaction may be 60-95°C, for example 60°C, 65°C, 70°C, 78°C, 82°C, 90°C or 95°C.
[0083] In certain specific embodiments, the reaction temperature of the free radical polymerization reaction is 78-82°C.
[0084] In certain specific embodiments, the reaction temperature of the free radical polymerization reaction is 65-70°C.
[0085] In certain specific embodiments, the reaction temperature of the free radical polymerization reaction is 90-95°C.
[0086] In certain specific embodiments, the reaction temperature of the free radical polymerization reaction is 60-65°C.
[0087] In the present invention, the reaction time of the free radical polymerization reaction may be 30-120 min, for example, 30 min, 60 min or 120 min.
[0088] In the present invention, the free radical polymerization reaction can be carried out under a protective atmosphere. The protective atmosphere refers to a gas atmosphere that does not react with the reaction system, such as nitrogen or an inert gas.
[0089] In a third aspect, the present invention provides an acrylate polymer, which is prepared by the above-mentioned preparation method of the acrylate polymer.
[0090] In a fourth aspect, the present invention provides a dispersant, which comprises the above-mentioned acrylate polymer, a volatile small molecule amine compound and the solvent;
[0091] Wherein, the mass ratio of the acrylic ester polymer to the volatile small molecule amine compound is 100:(1-100).
[0092] In the present invention, the volatile small molecule amine compound can be selected conventionally in the art, preferably one or more of triethylamine, tri-n-butylamine, ethylenediamine, butanediamine, hexanediamine, monoethanolamine, monoisopropanolamine, n-propanolamine, N,N-dimethylethanolamine, 2-amino-2-methyl-1-propanol, hydroxyethylethylenediamine and hydroxyethylhydrazine, such as butanediamine, monoethanolamine, n-propanolamine, N,N-dimethylethanolamine or 2-amino-2-methyl-1-propanol.
[0093] In the present invention, the mass ratio of the acrylic acid ester polymer to the volatile small molecule amine compound may be 100:1, 100:5, 100:10, 100:29.9 or 100:89.7.
[0094] In the present invention, the mass ratio of the acrylate polymer to the solvent may be 100:(50-5000), preferably 100:(100-1000), for example, 100:139.9, 100:140, 100:140.1, 100:310.3, 100:370.1, 100:395.0, 100:399.0 or 100:890.
[0095] In the present invention, the preparation method of the dispersant comprises the following steps: mixing the acrylic ester polymer, the volatile small molecule amine compound and the solvent.
[0096] In a fifth aspect, the present invention provides an electrode slurry comprising an electrode material and the dispersant as described above.
[0097] In the present invention, the electrode material may be a carbon material or a carbon-coated material.
[0098] The carbon material may be selected conventionally in the art, such as one or more of carbon nanotubes, graphene, acetylene black, porous carbon and conductive carbon black.
[0099] The carbon-coated material may be selected conventionally in the art, such as one or both of carbon-coated lithium iron phosphate and carbon-coated lithium manganese iron phosphate.
[0100] The electrode slurry may include: the dispersant, the carbon material and the solvent. The mass ratio of the acrylate dispersant to the carbon material may be 12.5:(5.0-20.0), such as 12.5:5.0, 12.5:10.0 or 12.5:20.0.
[0101] Wherein, the electrode slurry may include: the dispersant, the carbon coating material, the binder, the conductive agent and the solvent. The mass ratio of the dispersant, the carbon coating material, the binder and the conductive agent may be (0.90-3.60):173.70:(3-4):(2-3), for example, 0.90:173.70:3.6:2.7, 1.80:173.70:3.6:2.7 or 3.60:173.70:3.6:2.7. The binder may be a conventional choice in the art, such as PVDF. The conductive agent may be a conventional choice in the art, such as SP.
[0102] In a fifth aspect, the present invention provides an electrode plate, which is made using the electrode slurry as described above.
[0103] In the present invention, the method for preparing an electrode plate using the electrode slurry can be conventional in the art, and generally comprises: coating the electrode slurry on at least one surface of a current collector, and drying.
[0104] In a sixth aspect, the present invention provides a battery comprising the electrode plate as described above.
[0105] In the present invention, the battery is preferably a lithium-ion battery.
[0106] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0107] The reagents and raw materials used in the present invention are commercially available.
[0108] The positive and progressive effects of the present invention are:
[0109] The present invention designs the structure of the repeating unit in the molecular chain of the acrylic ester polymer to obtain a novel acrylic ester polymer. The molecular chains of the acrylic ester polymer are all aliphatic, which can avoid increasing the rigidity of the polymer chain segment and help to obtain excellent dispersion viscosity reduction and viscosity stabilization effects. First, the acrylic ester monomer M-1 is conducive to the formation of a firm adsorption of the dispersant on the carbon material or the carbon-coated material; secondly, the acrylic monomer M-2 interacts with the volatile small molecule amine compound B to enhance the adsorption effect and provide a charge repulsion effect; furthermore, the acrylic acid methoxy-terminated polyether monomer M-3 has good chemical stability and better chain segment flexibility compared with the existing methoxy polyethylene glycol acrylate monomer. Based on this, the dispersant of the present invention is used in the process of preparing the electrode slurry, which has excellent dispersion viscosity reduction and viscosity stabilization effects, and further improves the quality stability of the battery. DETAILED DESCRIPTION
[0110] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0111] In the following synthesis examples and comparative synthesis examples:
[0112] (1) Weight average molecular weight and molecular weight distribution index (PDI)
[0113] The weight average molecular weight and molecular weight distribution index of the polymer are tested by using a Waters 1515 gel permeation chromatograph, calibrated with standard polystyrene, and using N-methylpyrrolidone as the mobile phase at a column temperature of about 90°C.
[0114] (2) Solid content
[0115] Solid content refers to the mass percentage of solids in a slurry or solution.
[0116] Synthesis Example 1
[0117] 300.0 g of propylene glycol methyl ether acetate was added to a 2000 ml four-necked flask equipped with a stirrer, a thermometer, a reflux condenser, and a dropping device, and the mixture was heated to 80° C. with stirring.
[0118] At the same time, an initiator solution obtained by dissolving 6.0 g of benzoyl peroxide in 188.0 g of propylene glycol methyl ether acetate and a monomer solution obtained by dissolving 780.0 g of lauryl methacrylate (M-1), 180.0 g of acrylic acid (M-2), 240.0 g of polyethylene glycol (n=9) allyl methyl ether (M-3), and 6.0 g of n-dodecyl mercaptan in 300.0 g of propylene glycol methyl ether acetate were dripped, and the dripping time was controlled at 420 minutes and 360 minutes respectively, and the reaction temperature was controlled at 78-82° C. After the dripping was completed, the mixture was kept warm at 78-82° C. for 120 minutes to complete the polymerization reaction. After the insulation was completed, the mixture was cooled to below 50° C. to obtain a polymer solution containing an acrylate polymer (A-1) with a solid content of 60.2%.
[0119] The weight average molecular weight of the acrylic acid ester polymer (A-1) was 49,600, and the molecular weight distribution index (PDI) was 1.92.
[0120] Synthesis Example 2
[0121] 300.0 g of N,N-dimethylformamide was added to a 2000 ml five-necked flask equipped with a stirrer, a N2 inlet tube, a thermometer, a reflux condenser, and a dropping device. The air in the four-necked flask was replaced by N2, and the mixture was stirred and heated to 65°C.
[0122] At the same time, an initiator solution prepared by dissolving 3.0 g of azobisisobutyronitrile in 295.0 g of N,N-dimethylformamide and a monomer solution prepared by dissolving 400.0 g of stearyl acrylate (M-1), 100.0 g of acrylic acid (M-2), 500.0 g of polyethylene glycol (n=16) vinyl methyl ether (M-3), and 2.0 g of mercaptoethanol in 400.0 g of N,N-dimethylformamide were added dropwise, and the addition time was controlled at 420 minutes and 360 minutes, respectively, and the reaction temperature was controlled at 65-70°C. After the addition was completed, the mixture was kept at 65-70°C for 60 minutes to complete the polymerization reaction. After the insulation was completed, the mixture was cooled to below 50°C to obtain a polymer solution containing an acrylate polymer (A-2) with a solid content of 50.1%.
[0123] The weight average molecular weight of the acrylic acid ester polymer (A-2) was 36,200, and the molecular weight distribution index (PDI) was 1.85.
[0124] Synthesis Example 3
[0125] 300.0 g of butyl acetate was added to a 2000 ml four-necked flask equipped with a stirrer, a thermometer, a reflux condenser, and a dropping device, and the mixture was heated to 90° C. with stirring.
[0126] At the same time, an initiator solution obtained by dissolving 3.0 g of azobisisoheptanenitrile in 296.4 g of butyl acetate and a monomer solution obtained by dissolving 180.0 g of docosyl acrylate (M-1), 120.0 g of methacrylic acid (M-2), 300.0 g of polypropylene glycol (n=20) allyl butyl ether (M-3), and 0.6 g of 3-mercaptopropionic acid octyl ester in 800.0 g of butyl acetate were added dropwise, and the dropping time was controlled at 420 minutes and 360 minutes respectively, and the reaction temperature was controlled at 90-95° C. After the dropping was completed, the mixture was kept warm at 90-95° C. for 30 minutes to complete the polymerization reaction. After the insulation was completed, the mixture was cooled to below 50° C. to obtain a polymer solution containing an acrylate polymer (A-3) with a solid content of 30.1%.
[0127] The weight average molecular weight of the acrylic acid ester polymer (A-3) was 68,300, and the molecular weight distribution index (PDI) was 2.15.
[0128] Synthesis Example 4
[0129] 300.0 g of N-methylpyrrolidone was added to a 2000 ml four-necked flask equipped with a stirrer, a thermometer, a reflux condenser and a dropping device, and the air in the four-necked flask was replaced by N2. The mixture was stirred and heated to 60°C.
[0130] At the same time, an initiator solution obtained by dissolving 6.0 g of 4,4'-azobis(4-cyanovaleric acid) in 190.4 g of N-methylpyrrolidone and a monomer solution obtained by dissolving 720.0 g of hexadecyl acrylate (M-1), 60.0 g of acrylic acid (M-2), 360.0 g of allyl polyethylene glycol polypropylene glycol (n=45) acetate (M-3), 60.0 g of styrene, and 3.6 g of 3-mercaptopropionic acid in 300.0 g of N-methylpyrrolidone were added dropwise, and the dropping time was controlled at 420 minutes and 360 minutes, respectively, and the reaction temperature was controlled at 60-65°C. After the dropping was completed, the temperature was kept at 60-65°C for 120 minutes to complete the polymerization reaction. After the insulation was completed, the temperature was lowered to below 50°C to obtain a polymer solution containing an acrylate polymer (A-4) with a solid content of 59.9%.
[0131] The weight average molecular weight of the acrylic acid ester polymer (A-4) was 28,100, and the molecular weight distribution index (PDI) was 1.65.
[0132] Synthesis Example 5
[0133] 300.0 g of N,N-dimethylformamide was added to a 2000 ml four-necked flask equipped with a stirrer, a thermometer, a reflux condenser, and a dropping device, and the mixture was stirred and heated to 60°C.
[0134] At the same time, an initiator solution obtained by dissolving 6.0 g of benzoyl peroxide in 190.2 g of N,N-dimethylformamide, a reducing agent solution obtained by dissolving 3.0 g of N,N-dimethylaniline in 100.0 g of N,N-dimethylformamide, and a monomer solution obtained by dissolving 200.0 g of stearyl acrylate (M-1), 300.0 g of lauryl methacrylate (M-1), 100.0 g of acrylic acid (M-2), 400.0 g of methallyl polyethylene glycol (n=6) acetate (M-3), and 0.8 g of mercaptoethanol in 400.0 g of N,N-dimethylformamide were added dropwise, and the dropping time was controlled at 420 minutes, 420 minutes, and 360 minutes, respectively, and the reaction temperature was controlled at 60-65° C. After the dropping was completed, the mixture was kept at 60-65° C. for 60 minutes to complete the polymerization reaction. After the heat preservation was completed, the temperature was lowered to below 50° C. to obtain a polymer solution containing an acrylic acid ester polymer (A-5) with a solid content of 50.2%.
[0135] The weight average molecular weight of the acrylic acid ester polymer (A-5) was 52,800, and the molecular weight distribution index (PDI) was 1.75.
[0136] Comparative Synthesis Example 1
[0137] Compared with Synthesis Example 2, the only difference is that stearyl acrylate is replaced by isooctyl acrylate to obtain a polymer solution containing polymer P-1 with a solid content of 50.0%, a weight average molecular weight of 37100 and a molecular weight distribution index (PDI) of 1.83.
[0138] Comparative Synthesis Example 2
[0139] Compared with Synthesis Example 4, the only difference is that the monomer solution is replaced with a monomer solution obtained by dissolving 240.0 g of hexadecyl acrylate, 60.0 g of acrylic acid, 840.0 g of allyl polyethylene glycol polypropylene glycol (n=45) acetate, 60.0 g of styrene, and 3.6 g of 3-mercaptopropionic acid in 300.0 g of N-methylpyrrolidone to obtain a polymer solution containing polymer P-2, which has a solid content of 59.5%, a weight-average molecular weight of 27,300, and a molecular weight distribution index (PDI) of 1.63.
[0140] Comparative Synthesis Example 3
[0141] The acrylic ester comb dispersant prepared in Example 5 of the invention patent CN115975104A is marked as P-3. The obtained polymer solution has a solid content of 47.3%, a weight average molecular weight of 52300, and a molecular weight distribution index of 2.13.
[0142] Comparative Synthesis Example 4
[0143] Compared with Synthesis Example 1, the only difference is that 240.0 g of polyethylene glycol (n=9) allyl methyl ether (M-3) in the monomer solution is replaced with 240.0 g of methoxy polyethylene glycol (n=9) acrylate to obtain a polymer solution containing polymer P-4 with a solid content of 60.2%, a weight-average molecular weight of 51,300 and a molecular weight distribution index of 1.96.
[0144] The main raw materials in the synthesis examples and comparative examples are summarized in Table 1.
[0145] Table 1
[0146]
[0147] Preparation Example and Comparative Example
[0148] The polymer solutions obtained in Synthesis Examples 1-5 and Comparative Synthesis Examples 1-5, PVP K30 (Luvitec K30 from BASF GmbH, Germany), volatile small molecule amine compound B and solvent C were uniformly mixed in the mass ratio shown in Table 2 to obtain dispersants D01-D09 in Preparation Examples 1-9 of the present invention and dispersants D10-D15 in Preparation Comparative Examples 1-6, and the preparation results are shown in Table 3. It should be noted that since the polymer solution itself contains a certain amount of solvent, the amount of solvent in Table 2 is the amount of additional solvent, and the content of the solvent in Table 3 is the total content of the solvent in the dispersant.
[0149] Table 2 Dispersant preparation raw materials in preparation examples and preparation comparative examples
[0150]
[0151] Table 3 Dispersant compositions in preparation examples and comparative examples
[0152]
[0153]
[0154] Application example 1: Electrode slurry containing carbon nanotubes (CNT)
[0155] Carbon nanotubes H (CNT) are used, and their main technical indicators are shown in Table 4.
[0156] Table 4 Technical indicators of carbon nanotube H (CNT)
[0157] project Specific surface area Pipe diameter length purity pH Fe content Other metal element content Test Results <![CDATA[240m 2 / g]]> 10-12nm <15μm ≥99.5% 6.43 ≤300ppm ≤5ppm
[0158] Use a ball mill to grind and disperse according to the scheme in Table 5. After all the CNTs are added, the grinding is completed for 3 hours to obtain an electrode slurry containing CNTs (referred to as CNT slurry).
[0159] Table 5 CNT slurry preparation scheme
[0160]
[0161] The rotational viscosity of the CNT slurry in Table 5 was tested using a rotational viscometer 1 hour, 24 hours, 3 days, 7 days, 14 days, and 30 days after grinding. The results are shown in Table 6.
[0162] Reference standard: GB / T 10247-2008 viscosity test method, instrument model: DV-2TLV Brookfield viscometer, key parameters are as follows:
[0163] Rotor: selected according to viscosity range; rotation speed: 60rpm; time: 3min; test temperature: 25℃.
[0164] Table 6 Rotational viscosity of CNT slurry after storage for different time periods (viscosity unit: mPa·s)
[0165]
[0166] Note: X indicates that a uniform slurry cannot be obtained, and ※ indicates that the slurry is gelled
[0167] From the data comparison of CNT-D02 and CNT-D10 slurries, it can be preliminarily seen that when preparing the dispersant P1 in the CNT-D10 slurry, the M-1 monomer in the synthetic comparative example 1 is isooctyl acrylate, that is, the carbon chain length is only 8, which is lower than the carbon chain length of R1 in the synthetic example 2, and cannot play the role of reducing and stabilizing viscosity, which will cause the slurry to gel.
[0168] From the data comparison of CNT-D03, CNT-D06, CNT-D07, CNT-D08 and CNT-D09 slurries and the data comparison of CNT-D12 and CNT-D13 slurries, it can be preliminarily seen that when preparing the dispersant in the slurry, with the increase of the proportion of volatile small molecule amines, the viscosity reduction and viscosity stabilization effects first increase and then decrease. In CNT-D08 slurry, when the weight proportion of volatile small molecule amines in the dispersant is 9.0 parts, that is, 9wt% of the polymer, the viscosity reduction and viscosity stabilization effects achieve excellent results.
[0169] From the data comparison of CNT-D04 and CNT-D11 slurries, it can be preliminarily seen that when preparing the dispersant P2 in the CNT-D11 slurry, in the synthetic comparative example 2, the mass percentage of the M-3 monomer allyl polyethylene glycol polypropylene glycol (n=45) acetate reached 70%, which resulted in a significant decrease in the viscosity reduction and viscosity stabilization effects.
[0170] From the data comparison of CNT-D05 and CNT-D15 slurries, it can be preliminarily seen that when preparing the dispersant P4 in the CNT-D15 slurry, in the synthetic comparative example 4, the M-3 monomer uses methoxy polyethylene glycol acrylate, that is, the group connected to the main chain carbon is changed from the alkylene group in the synthetic example 1 to the carbonyl group, which greatly reduces the viscosity reduction and viscosity stabilization effects.
[0171] In summary, from the results in Table 6, it can be seen that the viscosity reduction and viscosity stabilization effects of CNT-D01 to CNT-D09 slurries obtained by using the dispersant of the preparation example are significantly better than those of CNT-D10 to CNT-D15 obtained by using the dispersant of the preparation comparative example.
[0172] Application Example 2: Electrode slurry containing carbon-coated lithium iron phosphate (C@LFP)
[0173] The lithium iron phosphate product 10P (C@LFP) is used, and its main technical indicators are shown in Table 7.
[0174] Table 7 Technical indicators of lithium iron phosphate products 10P
[0175] project Specific surface area D50 D90 Carbon content pH First charge capacity First discharge capacity Test Results <![CDATA[13.1m 2 / g]]> 1.26μm 4.28μm 1.15% 9.0 161.9mAh / g 156.3mAh / g
[0176] Use a homogenizer to perform homogenization and dispersion according to the scheme in Table 8 to obtain an electrode slurry containing C@LFP (referred to as C@LFP slurry).
[0177] Table 8 Homogenization scheme of C@LFP slurry
[0178]
[0179] The rotational viscosity of the C@LFP slurry in Table 8 was tested after 1 hour of discharge and 24 hours of storage. The results are shown in Table 9.
[0180] Reference standard: GB / T 10247-2008 viscosity test method, instrument model: DV-2TLV Brookfield viscometer, key parameters are as follows:
[0181] Rotor: selected according to viscosity range; rotation speed: 60rpm; time: 3min; test temperature: 25℃.
[0182] Table 9 Rotational viscosity of C@LFP slurry
[0183] C@LFP slurry number 1h rotational viscosity, mPa·s 24h rotational viscosity, mPa·s 10P-0 10200 47500 10P-D01 9800 15200 10P-D02 9200 13800 10P-D03 9500 14700 10P-D04 9300 12900 10P-D05 8700 12600 10P-D06 10800 15600 10P-D07 10100 15200 10P-D08 9450 14300 10P-D09 9300 14500 10P-D10 16000 91000 10P-D11 13600 62000 10P-D12 18000 107000 10P-D13 17500 98600 10P-D14 18500 43200 10P-D15 11200 21600
[0184] From the data comparison of 10P-D02 and 10P-D10 slurries, it can be preliminarily seen that when preparing the dispersant P1 in the 10P-D10 slurry, the M-1 monomer used in the synthetic comparative example 1 is isooctyl acrylate, that is, the carbon chain length is only 8, which is lower than the carbon chain length of R1 in the synthetic example 2, and cannot play the role of viscosity reduction and viscosity stabilization.
[0185] From the data comparison of 10P-D03, 10P-D06, 10P-D07, 10P-D08 and 10P-D09 slurries, it can be preliminarily seen that when preparing the dispersant in the slurry, with the increase of the proportion of volatile small molecule amines, the viscosity reduction and viscosity stabilization effects first increase and then decrease. In 10P-D03, 10P-D08 and 10P-D09 slurries, when the weight proportion of volatile small molecule amines in the dispersant is 3-27 parts, that is, 3wt%-27wt% of the polymer, the viscosity reduction and viscosity stabilization effects achieve better results.
[0186] From the data comparison of 10P-D04 and 10P-D11 slurries, it can be preliminarily seen that when preparing the dispersant P2 in the 10P-D11 slurry, compared with Synthesis Example 2, the mass percentage of the M-3 monomer allyl polyethylene glycol polypropylene glycol (n=45) acetate reached 70%, resulting in a significant decrease in the viscosity reduction and viscosity stabilization effects.
[0187] From the data comparison of 10P-D05 and 10P-D15 slurries, it can be preliminarily seen that when preparing the dispersant P4 in the 10P-D15 slurry, in the synthetic comparative example 4, the M-3 monomer adopts methoxy polyethylene glycol acrylate, that is, the group connected to the main chain carbon is changed from the alkylene group in the synthetic example 1 to the carbonyl group, which greatly reduces the viscosity reduction and stabilization effects.
[0188] In summary, from the results in Table 9, it can be seen that the viscosity reducing and stabilizing effects of slurries 10P-D01 to 10P-D09 obtained by using the dispersant of the preparation example are significantly better than those of slurries 10P-D10 to 10P-D15 obtained by using the dispersant of the preparation comparative example.
[0189] The present invention illustrates the detailed method of the present invention through the above embodiments, but it does not mean that the present invention must rely on the above embodiments. The embodiments in this part are only exemplary and explanatory and should not have any limiting effect on the protection scope of the present invention.
Claims
1. An acrylate polymer, characterized in that It comprises a repeating unit I, a repeating unit II and a repeating unit III; based on the total mass of the acrylic ester polymer, the mass percentage of the repeating unit I is 30.0%-70.0%; the mass percentage of the repeating unit III is 20.0%-60.0%; The structure of the repeating unit I is shown in formula (I): In each repeating unit I, R1 is each independently hydrogen or methyl; R2 is each independently C 10 -C 25 The alkyl group; The structure of the repeating unit II is shown in formula (II): In each repeating unit II, R3 are each independently hydrogen or methyl; Z is each independently hydrogen, Li + 、Na + , K + NH4 + or organic amine groups with a molecular weight of less than 150; The structure of the repeating unit III is shown in formula (III): In each repeating unit III, R4 are each independently hydrogen or methyl; A groups are each independently -(CH2) p1 -; In each A group, p1 is independently an integer from 0 to 2; The B groups are each independently In each B group, R5 is independently hydrogen or methyl, and R6 is independently hydrogen, C1-C 18 The alkyl group is C2-C6 or the acyl group is C2-C6, and n1 is 4-70 each independently.
2. The acrylate polymer according to claim 1, characterized in that In the acrylic ester polymer, repeating unit I, repeating unit II and repeating unit III are randomly distributed; and / or, the weight average molecular weight of the acrylate polymer is 10,000-70,000, such as 28,100, 36,200, 49,600, 52,800 or 68,300; And / or, in each repeating unit I, R1 and R2 each independently satisfy any one of the following conditions ①-⑤: ① R2 is independently C 12 -C 25 The alkyl group is preferably C 16 -C 22 Alkyl groups, such as C 18 The alkyl group; ②R1 is methyl; R2 is C 12 The alkyl group; ③R1 is hydrogen; R2 is C 18 The alkyl group; ④R1 is hydrogen; R2 is C 22 The alkyl group; ⑤R1 is hydrogen; R2 is C 16 The alkyl group; And / or, in each repeating unit II, R3 and Z satisfy any one of the following conditions ①-②: ① R3 is hydrogen, Z is hydrogen; ②R3 is methyl; Z is hydrogen; And / or, in each repeating unit III, the A group, the B group, R4, R5, R6, p1, and n1 satisfy any one of the following conditions ①-⑧: ① In each A group, p1 is 0 or 1; ② In each B group, R6 is methyl, butyl or acetyl; ③ In each B group, n1 is 6-45, for example, 6, 9, 16, 20 or 45; ④R4 and R5 are both hydrogen; R6 is methyl; p1 is 1; ⑤R4 and R5 are both hydrogen; R6 is methyl; p1 is 0; ⑥R4 is hydrogen; R5 is methyl; R6 is butyl; p1 is 1; ⑦R4 is hydrogen; R5 is hydrogen or methyl; R6 is acetyl; p1 is 1; ⑧R4 is methyl; R5 is hydrogen; R6 is acetyl; p1 is 1.
3. A method for preparing an acrylate polymer, characterized in that: It includes the following steps: The raw materials are subjected to a free radical polymerization reaction to obtain the product; wherein the raw materials include polymerizable monomers, and the polymerizable monomers include monomer M-1, monomer M-2 and monomer M-3; based on the total mass of the polymerizable monomers, the mass percentage of the monomer M-1 is 30.0%-70.0%; the mass percentage of the monomer M-3 is 20.0%-60.0%; The structure of the monomer M-1 is shown in formula M-1: Wherein, R1 and R2 are as defined in claim 1 or 2; the structure of the monomer M-2 is shown in formula M-2: Wherein, R3 and Z are as defined in claim 1 or 2; the structure of the monomer M-3 is shown in formula M-3: wherein A, B and R4 are as defined in claim 1 or 2.
4. The method for preparing an acrylate polymer according to claim 3, wherein: The monomer M-1 is one or more of lauryl methacrylate, stearyl acrylate, behenyl acrylate and hexadecyl acrylate; and / or, the mass percentage of the monomer M-1 is 30.0%, 40.0%, 50.0%, 60.0% or 65.0%; and / or, the monomer M-2 is acrylic acid or methacrylic acid; and / or, the mass percentage of the monomer M-2 is 2.0%-20.0%, such as 5.0%, 10.0%, 15.0% or 20.0%; and / or, the monomer M-3 is polyethylene glycol allyl methyl ether, polyethylene glycol vinyl methyl ether, polypropylene glycol allyl butyl ether, allyl polyethylene glycol polypropylene glycol acetate or methallyl polyethylene glycol acetate; and / or, the mass percentage of the monomer M-3 is 20.0%-50.0%, for example 20.0%, 30.0%, 40.0% or 50.0%; and / or, the sum of the mass percentages of the monomer M-1, the monomer M-2 and the monomer M-3 is 90.0%-100.0%, for example 95.0% or 100.0%; And / or, the polymerizable monomer further comprises a monomer M-4; the monomer M-4 is preferably styrene; And / or, the polymerizable monomers do not include monomers containing amine groups.
5. The method for preparing an acrylate polymer according to claim 3, wherein: The free radical polymerization reaction is carried out in a solvent; the solvent is preferably one or more of ethyl acetate, butyl acetate, propylene glycol methyl ether acetate, N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone, such as propylene glycol methyl ether acetate, N,N-dimethylformamide, butyl acetate or N-methylpyrrolidone; And / or, the raw material further comprises an initiator and a chain transfer agent; Preferably, the initiator is a peroxide initiator, an azo initiator, or a redox initiator composed of a peroxide initiator and a reducing agent; the peroxide initiator is preferably dibenzoyl peroxide, dilauroyl peroxide, diisopropylbenzene peroxide, isopropylbenzene hydroperoxide, methyl ethyl ketone peroxide, tert-butyl hydroperoxide, di-tert-butyl peroxide, tert-butyl peroxytivalate, tert-butyl peroxypivalate, tert-butyl peroxyisobutyrate, tert-butyl peroxide (2-ethylhexanoate), 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, tert-butyl peroxy-3,5,5-trimethylhexanoate, tert-butyl peroxide isopropylbenzene or 1,4-di-tert-butyl peroxyisopropylbenzene; the azo initiator is preferably azodiisopropylbenzene. Butyronitrile, azobisisovaleronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, 1,1'-azo(cyanocyclohexane), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), azobisimidazolinylpropane, 2,2'-azobis(N-butyl 2-methylpropionamide), 2,2'-azo(2-methyl-N-(2-hydroxyethyl)propionamide), 2,2-azobisisobutylamidine dihydrochloride or 2,2'-azabis(2-imidazoline) dihydrochloride; the reducing agent is preferably an amine compound, more preferably tetramethylethylenediamine, N,N-dimethylaniline, N,N-dimethyl-p-toluidine, ethylenediamine, diethylenetriamine, triethylenetetramine or tetraethylenepentamine; Preferably, the initiator is added dropwise into the reaction system in the form of an initiator solution; the time of the addition is more preferably 360-420 min; Preferably, the chain transfer agent is one or more of a mercaptocarboxylic acid chain transfer agent, a thiol chain transfer agent, isopropanol and hypophosphorous acid; the mercaptocarboxylic acid chain transfer agent is more preferably thioglycolic acid, 3-mercaptopropionic acid, ethyl 3-mercaptopropionate, butyl 3-mercaptopropionate, octyl 3-mercaptopropionate or trimethylolpropane tris(3-mercaptopropionic acid); the thiol chain transfer agent is more preferably mercaptoethanol, butyl mercaptan, hexyl mercaptan, octyl mercaptan or dodecanol; Preferably, the chain transfer agent is added dropwise into the reaction system in the form of a monomer solution; the monomer solution more preferably comprises a polymerizable monomer and the chain transfer agent; the addition time is more preferably 360-420 min; And / or, the reaction temperature of the free radical polymerization reaction is 60-95° C.; the reaction temperature of the free radical polymerization reaction preferably satisfies any one of the following conditions ①-④: ① The reaction temperature of the free radical polymerization reaction is 78-82°C; ② The reaction temperature of the free radical polymerization reaction is 65-70°C; ③ The reaction temperature of the free radical polymerization reaction is 90-95°C; ④ The reaction temperature of the free radical polymerization reaction is 60-65°C; And / or, the reaction time of the free radical polymerization reaction is 30-120 min, for example 30 min, 60 min or 120 min; And / or, the free radical polymerization reaction is carried out under a protective atmosphere; the protective atmosphere is preferably nitrogen or an inert gas.
6. An acrylate polymer, characterized in that The acrylic acid ester polymer is obtained by the preparation method of the acrylic acid ester polymer according to any one of claims 3 to 5.
7. A dispersant, characterized in that: It comprises the acrylic ester polymer as claimed in any one of claims 1, 2 and 6, a volatile small molecule amine compound and a solvent; Wherein, the mass ratio of the acrylic ester polymer to the volatile small molecule amine compound is 100:(1-100).
8. The dispersant according to claim 7, characterized in that The volatile small molecule amine compound is one or more of triethylamine, tri-n-butylamine, ethylenediamine, butanediamine, hexanediamine, monoethanolamine, monoisopropanolamine, n-propanolamine, N,N-dimethylethanolamine, 2-amino-2-methyl-1-propanol, hydroxyethylethylenediamine and hydroxyethylhydrazine, such as butanediamine, monoethanolamine, n-propanolamine, N,N-dimethylethanolamine or 2-amino-2-methyl-1-propanol; and / or, the mass ratio of the acrylic acid ester polymer to the volatile small molecule amine compound is 100:1, 100:5, 100:10, 100:29.9 or 100:89.7; and / or, the mass ratio of the acrylate polymer to the solvent is 100:(50-5000), preferably 100:(100-1000), for example 100:139.9, 100:140, 100:140.1, 100:310.3, 100:370.1, 100:395.0, 100:399.0 or 100:890; And / or, the solvent is one or more of ethyl acetate, butyl acetate, propylene glycol methyl ether acetate, N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone, such as propylene glycol methyl ether acetate, N,N-dimethylformamide, butyl acetate or N-methylpyrrolidone.
9. An electrode slurry, characterized in that: It comprises an electrode material and the dispersant according to claim 7 or 8.
10. The electrode slurry according to claim 9, characterized in that The electrode material is a carbon material or a carbon-coated material; Preferably, the carbon material is one or more of carbon nanotubes, graphene, acetylene black, porous carbon and conductive carbon black; Preferably, the carbon-coated material is one or both of carbon-coated lithium iron phosphate and carbon-coated lithium manganese iron phosphate; Preferably, the electrode slurry is any one of the systems ① and ②: ① The electrode slurry comprises: the dispersant, the carbon material and the solvent; the mass ratio of the dispersant to the carbon material is preferably 12.5:(5.0-20.0), such as 12.5:5.0, 12.5:10.0 or 12.5:20.0; ② The electrode slurry comprises: the dispersant, the carbon-coated material, the binder, the conductive agent and the solvent; the mass ratio of the dispersant, the carbon-coated material, the binder and the conductive agent is preferably (0.90-3.60):173.70:(3-4):(2-3), for example, 0.90:173.70:3.6:2.7, 1.80:173.70:3.6:2.7 or 3.60:173.70:3.6:2.7; the binder is preferably PVDF; the conductive agent is preferably SP.
11. An electrode plate, characterized in that: The electrode slurry is prepared using the electrode slurry as claimed in claim 9 or 10.
12. A battery, characterized in that: It comprises the electrode plate as claimed in claim 11.
Citation Information
Patent Citations
Acrylate comb dispersant and preparation method thereof
CN115975104A
Dispersant composition for electricity storage device electrode
CN116390976A